The Impact of Entrepreneurial Networks on The Performance of Small Business in Nigeria - Aladejebi, Olufemi (Archives of Business Research, 2020)
Networking is ultimately the process of exchanging information between two or more people; in this case, entrepreneurs. The main objective of this paper is to look into the firm attributes related to formal networking and investigate whether membership in formal networks in the form of business associations and industry/trade-specific associations has been an impact on the growth of SMEs business in Lagos, Nigeria. A purposeful sample was used to select respondents. Questionnaires designed to examine the views of the entrepreneur about SME networking were distributed amongst two SME groups, namely Nigerian Association Of Small Scale Industrialists (NASSI), Lagos, and PHARMALLIANCE (Association of Community Pharmacists). The research instrument was based on a five-point Likert scale. The questionnaire administered contained 2parts, Part 1: contains general information, while Part 2: contains specific questions relating to networking. The results of the analysis showed a generally positive overview of SME networking in Nigeria. The respondents mostly agree across both groups that networking is of great benefit to their businesses.